2008
DOI: 10.1038/ijo.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histaminergic manipulation on weight in obese adults: a randomized placebo controlled trial

Abstract: Objective: To determine the magnitude and determinants of weight loss in humans exposed to betahistine, a centrally acting histamine-1 (H-1) agonist and partial histamine-3 (H-3) antagonist. Design: A multicenter randomized, placebo-controlled dose-ranging weight loss trial with a 12-week treatment period. Subjects: Two hundred and eighty-one obese but otherwise healthy participants. Measurements: Weight and obesity-related comorbidities at baseline and at the end of the intervention. Results: Betahistine, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
1
35
1
Order By: Relevance
“…These clinical findings correspond with the results of animal studies, in which it was demonstrated that the co-treatment with betahistine partially reduced olanzapine-induced weight gain sideeffects [169]. It is worthy to note that histaminergic modulation may counterbalance druginduced overfeeding and weight gain, however it may be ineffective when there is no drugdependent alteration as showed in clinical trials in obese (otherwise health) subjects [172,171]. Therefore, it is not clear whether it could be useful as a weight-loss medication in obese non-medicated people.…”
Section: Clinical Trials For Co-treatment Of Betahistine and Olanzapisupporting
confidence: 74%
See 2 more Smart Citations
“…These clinical findings correspond with the results of animal studies, in which it was demonstrated that the co-treatment with betahistine partially reduced olanzapine-induced weight gain sideeffects [169]. It is worthy to note that histaminergic modulation may counterbalance druginduced overfeeding and weight gain, however it may be ineffective when there is no drugdependent alteration as showed in clinical trials in obese (otherwise health) subjects [172,171]. Therefore, it is not clear whether it could be useful as a weight-loss medication in obese non-medicated people.…”
Section: Clinical Trials For Co-treatment Of Betahistine and Olanzapisupporting
confidence: 74%
“…Barak and colleagues conducted a multicentre randomized, placebo-controlled weight loss trial using betahistine (16,32,48 mg/day) in 281 obese adults for a 12-week treatment [171]. The overall results revealed that betahistine did not induce significant weight loss in obese participants at the above dosages, while the prevalence of adverse events was low.…”
Section: Clinical Trials For Co-treatment Of Betahistine and Olanzapimentioning
confidence: 99%
See 1 more Smart Citation
“…43 In 2008, a study reported a significant weight reduction in women aged less than 50 years who received 48 mg betahistine/day rather than a placebo throughout a 12-week randomized controlled trial. 44 In 2012; a review regarded betahistine as one of the drug candidates for future role as a centrally acting anti-obesity medications. 45 In this study, administration of betahistine (along with low calorie diet and medium intensity exercise) caused a significant reduction in FPG, HbA1c%, Cpeptide, IR and functioning Beta Cell percent.…”
Section: Discussionmentioning
confidence: 99%
“…21 While claims have been made that Betahistine is associated with weight loss, these appear to be unfounded. 22 …”
Section: Marketed Preparations Of H 3 R Antagonist Betahistinementioning
confidence: 99%